KELAYAKAN USAHATANI BAYAM (Amaranthus spp) MEDIA PASIR DESA ABUMBUN JAYA KECAMATAN SUNGAI TABUK KABUPATEN BANJAR - Fitri Mahyudi; Husinsyah Husinsyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
This Research aim to know technically about effort management spinach farming evaluated from technical aspect in Abumbun Jaya Village Sungai Tabuk Subdistrict Banjarbaru City South Kalimantan Province and to know about cost, acceptance, revenue and spinach farming Feasibility. Pursuant to result of seen from technical management spinach farming still relative modestly, this seen from farm processing until the conservancy. Production obtained from 25 spinach farmer responder with wide mean equal to 352.236,45kg/ farmer. Productivity 1.030,64kg. Total Revenue with mean Rp. 5.668.520 per farmer. RCR Value spinach farming 1.67 competent so that to be feasible (RCR >1).